1972
DOI: 10.1111/j.1755-3768.1972.tb05981.x
|View full text |Cite
|
Sign up to set email alerts
|

A GENETIC STUDY OF CONGENITAL HEREDITARY MACULAR DEGENERATION IN THE COUNTY OF VäSTERBOTTEN, SWEDEN

Abstract: Two pedigrees of two separate families are presented. In one of them, hereditary macular degeneration was confirmed in 24 out of 43 cases examined ophthalmologically. They belonged to 3 generations. By means of the parish catechetical meeting examination records, it has ‐ to a rather high degree of accuracy ‐ been possible to follow the disease back another 4 generations to the 18th century. In the other family, there were 6 patients with congenital macular degeneration. It was only possible to follow the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1980
1980
1980
1980

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Very thorough reviews may be found elsewhere (Deutman 1971;Krill 1977). A Swedish pedigree with VMD was described by Barkman (1961); Nordstrom et al (1972) and others.…”
mentioning
confidence: 99%
“…Very thorough reviews may be found elsewhere (Deutman 1971;Krill 1977). A Swedish pedigree with VMD was described by Barkman (1961); Nordstrom et al (1972) and others.…”
mentioning
confidence: 99%